Enhancing multimodal literacy through community service learning in higher education - de Oliveira, Janaina Minelli (Frontiers in Education, 2024)
This Curriculum, Instruction, and Pedagogy (CIP) article outlines the pedagogical design of a course that uses Community Service Learning (CSL) to foster undergraduate students' multimodal literacy development. The article draws on a social semiotics approach to learning and communication and aligns with progressive pedagogical designs that prioritize learners' active participation. The course syllabus, methodological procedures, and assessment strategies are described. CSL serves as a means for higher education teachers to embrace civic and social responsibilities, promoting values such as solidarity and generosity through their teaching. This article examines the challenges and benefits associated with CSL and offers insights to inspire higher education teachers to adopt pedagogical designs based on creativity, solidarity, and generosity.